2021
DOI: 10.3389/fpls.2021.740414
|View full text |Cite
|
Sign up to set email alerts
|

Identification of High Nitrogen Use Efficiency Phenotype in Rice (Oryza sativa L.) Through Entire Growth Duration by Unmanned Aerial Vehicle Multispectral Imagery

Abstract: Identification of high Nitrogen Use Efficiency (NUE) phenotypes has been a long-standing challenge in breeding rice and sustainable agriculture to reduce the costs of nitrogen (N) fertilizers. There are two main challenges: (1) high NUE genetic sources are biologically scarce and (2) on the technical side, few easy, non-destructive, and reliable methodologies are available to evaluate plant N variations through the entire growth duration (GD). To overcome the challenges, we captured a unique higher NUE phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 105 publications
0
15
0
Order By: Relevance
“…In addition, high-throughput phenomics is being developed in the estimation of responses to nitrogen treatment in crops by using non-invasive imaging systems, spectroscopy, image analysis, robotics, enzyme-based sensors, etc. [75][76][77][78]. These methods can provide a large amount of real-time data, which will have a revolutionary impact on the estimation of phenotypes in the study of NUE in barley and will also be an important research direction.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…In addition, high-throughput phenomics is being developed in the estimation of responses to nitrogen treatment in crops by using non-invasive imaging systems, spectroscopy, image analysis, robotics, enzyme-based sensors, etc. [75][76][77][78]. These methods can provide a large amount of real-time data, which will have a revolutionary impact on the estimation of phenotypes in the study of NUE in barley and will also be an important research direction.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…There were only limited studies reported the attempts on the UAV-based estimation of N use efficiency, which for instance is reflected by the correlation between the UAV-based multispectral traits with NUE (Yang et al, 2020). (Liang et al, 2021) has revealed the capability of using UAV multispectral imagery for the identification of high N use efficiency phenotype in rice. Our results demonstrated that, by only using the latent variables extracted from UAV images, we could predict the NAE (Figure 12), highlighting the prospect of using of UAV-based images to estimate the indicators of NUE.…”
Section: Uav-based Predictions Of N Use Efficiencymentioning
confidence: 99%
“…The results revealed that the NDRE had a high consistency and accuracy for NUE, particularly in the mid to late-grain filling stage. In addition, the nitrogen dynamics time-series curves of the two rice populations were captured by UAVs’ multispectral imagery, which were used to identify an available spectral index (NDRE) and a high NUE variety ( Liang et al., 2021 ). Therefore, more studies are needed to explore the potential of UAVs imagery in NUE prediction.…”
Section: Introductionmentioning
confidence: 99%